Customer segmantation utilization for differentiated approach. - Panuš Jan; Jonášová Hana; Kantorová Kateřina; Horáčková Kateřina; Doležalová Martina (IEEE (Institute of Electrical and Electronics Engineers), 2016)
Customer segmentation and customer relationship management generally is interesting subject to explore. One of the main reasons why we should focus on exploring this type of research is to notion of customer loyalty and profitability to increasing market share. Customer value can provide basic information for more targeted and personalized marketing. In this paper, combination of ABC and RFM (Recency, Frequency, and Monetary) is used to customer segmentation. What is unique is using data mining segmentation method later on to dividing customers to four segments. We used well known Two Step, Kohononen – maps and K-means methods. Results show possibility to use these combinations for customer segmentation and results for different segments can be used to explain marketing strategies of company.
Využití segmentace zákazníků pro diferencovaný přístup k nim.
Keywords: customer segmentation; data-mining; CRM; segmentace zákazníků; dolování dat; CRM